(untitled) (Research, Society and Development, 2021)
The virulence factors cagA and vacA, are closely related to the pathogenicity of Helicobacter pylori. These factors are widely studied and associated with a higher risk of developing several gastroduodenal clinical outcomes, such as gastric cancer. Besides presenting several genetic polymorphisms, which can vary according to the geographic region, leading to different levels of toxicity and clinical gastric manifestations. Through an integrative review of the literature we analyzed the clinical/epidemiological studies published between 2015 and 2020 in the LILACS, Scielo and PubMed databases, aiming to gather the most recent and important data on the various polymorphisms in the factors of virulence cagA and vacA and gastroduodenal clinical outcomes. Nineteen studies were identified that contemplated the objective of this review and a great variety of polymorphisms and genetic combinations of these virulence factors were observed in association with several clinical outcomes. It was also noted the existence of genetic profiles of prevalence of H. pylori strains and associations with distinct gastric pathologies in certain geographical regions. Although some conflicting results were identified, the understanding of these findings and the identification of possible contributing genes in gastric pathologies may serve as markers for the development of strategies for the prevention of these pathologies and better treatment efficacy.